2001
DOI: 10.3171/jns.2001.94.5.0765
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective and behavioral efficacy of nerve growth factor—transfected hippocampal progenitor cell transplants after experimental traumatic brain injury

Abstract: This study demonstrates that immortalized neural stem cells that have been retrovirally transduced to produce NGF can markedly improve cognitive and neuromotor function and rescue hippocampal CA3 neurons when transplanted into the injured brain during the acute posttraumatic period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
46
0
16

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(64 citation statements)
references
References 72 publications
2
46
0
16
Order By: Relevance
“…For example, C17.2 overexpressing GDNF (GDNF-C17.2) improved survival of transplanted cells, enhanced neuronal differentiation of these cells and promoted learning behavior of the TBI rats at 6 weeks after transplantation comparing to parental C17.2 cells (Bakshi et al, 2006). Similarly, HiB5 progenitor clone engineered to secrete NGF (NGF-HiB5), when transplanted peripheral to the TBI site, decreased apoptosis of the host hippocampal neurons and improved motor and cognitive function comparing to controls (Philips et al, 2001). …”
Section: Brain and Spinal Cord Injurymentioning
confidence: 99%
“…For example, C17.2 overexpressing GDNF (GDNF-C17.2) improved survival of transplanted cells, enhanced neuronal differentiation of these cells and promoted learning behavior of the TBI rats at 6 weeks after transplantation comparing to parental C17.2 cells (Bakshi et al, 2006). Similarly, HiB5 progenitor clone engineered to secrete NGF (NGF-HiB5), when transplanted peripheral to the TBI site, decreased apoptosis of the host hippocampal neurons and improved motor and cognitive function comparing to controls (Philips et al, 2001). …”
Section: Brain and Spinal Cord Injurymentioning
confidence: 99%
“…Although injury-induced cell death disrupts the circuit initially, our data call into question a causal relationship between protection of the CA3 neurons and postinjury performance in the MWM. Several groups have reported a treatment-related improvement in learning and/or memory after experimental TBI in conjunction with CA3 neuronal survival (Sanderson et al, 1999, Leoni et al, 2000, Kline et al, 2001, Philips et al, 2001, Floyd et al, 2002, Kline et al, 2002, Ozdemir et al, 2005, Statler et al, 2006. However, other reports have clearly documented learning deficits in brain-injured animals in the absence of discernable hippocampal damage (Lyeth et al, 1990) or the converse, an improvement in MWM performance after injury without CA3 neuroprotection (Dixon et al, 2003, Hoover et al, 2004.…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, grafting of exogenous stem cells may accelerate the natural regeneration process. Recent findings indicated that neural stem cell transplantation can be a viable approach for the treatment of brain trauma (4)(5)(6) or stroke (7)(8)(9)(10). However, it is still not completely understood how these cells, endogenous or exogenous, are involved in the brain repair process (11).…”
Section: Introductionmentioning
confidence: 99%